Features of legal regulation of subsoil use in the countries with state ownership on mineral resources - A. N. Lun’Kin (Известия высших учебных заведений: Геология и разведка)
The two main approaches to legal regulation of subsoil use are characterized. The specifics of solution of this problem in European countries, firstly, in Norway, in Gulf countries, Asian countries, Latin America countries is considered. The importance of the state ownership of mineral resources for the country budget to solve different crucial social-economical problems is shown. Among them there are problems of import substitution, raising the standard and quality of living, limitation of foreign capital expansion for the provision of country national safety.